Development of ATOBAT: an Android-BasedMedicinal Plant Application Using Google Sites andMIT App Inventor - Zalfa Nur Awali; Sugeng Supriyanto; Anwar Sodik; Muhammad Husnul Khuluq; Herniyatun (Department of Informatics Engineering, Universitas Muhammadiyah Purwokerto, 2025)
Indonesia, as a